EVALUATING THE IMPACT OF ENDOCRINE-DISRUPTING CHEMICALS ON FERTILITY IN WILDLIFE: FROM AMPHIBIANS TO MAMMALS - Kadhim, Sajjad Jawad; Sahib, Mohsin Abbas; Khlaif, Salam Mohammed; AL-Azzawi, Mustafa Kareem; Zubaidi, Nabaa Abbas (PT. Antis International Publisher, 2024)
Endocrine-disrupting chemicals are contaminants that interrelate with wildlife's endocrine systems, producing negative influences on reproductive health and growth. Industrial pollutants, medicines and pesticides are between the chemicals that have develop a main source of worry due to of their pervasiveness in the environment and capability to reason ecological damage. This study brings both present data on the effects of EDCs on reproductive health in a diversity of animal species, particularly birds, fish, frogs, and mammals. Amphibians, together their complex life cycles and pored skin are particularly susceptible to EDCs. In relation to studies, contact to chemicals such as atrazine able to damage sexual development, causing in slanted sex proportions and developmental irregularities. Fish, which are significant indicators of marine ecosystem health, exhibition changed sexual development and reproductive disappointments due to of EDCs like estrogenic compounds and PCBs. Birds are harmed via EDCs like DDT, which leading to reproductive failures and eggshell thinning, influencing general population health. Mammals, reaching from little rodents to enormous animals, developmental defects, display lower fertility and behavioral alterations in reply to EDC exposure. Such EDCs clearly and profoundly affect reproductive health via altering gene expression, blocking receptors and mimicking hormones. Studies provide wide-ranging insights for these pathways, while field investigations afford experimental evidence of the effects of EDCs. Bio-monitoring methods, like tissue analysis and health markers, are very important to determining exposure levels and results. Identifying the influence of EDCs on animal reproductive health is significant for conservation initiatives and emerging regulation. Effective regulations might contain limiting the usage of dangerous chemicals and establishing monitoring systems to checked EDC levels in environment and the animals. Conservation efforts must prioritize habitat management and refurbishment because offset the effects of EDCs and safeguard endangered species. This research confirms the requirement for ongoing research and work to address the issues presented via endocrine disruption in animal populations. The research will explore how toxic chemicals disturb nature reproduction via analyzing variations in mating habits, sexual development, and fertility. It will examine how these materials influence hormonal systems via inhibiting receptors and mimicking hormones. Additionally, the research will observe current legislation governing these chemicals, assess their effectiveness, and refer for greater animal protection.